Screening for liver cancer during transplant waiting list: a multicenter study from South America. Issue 3 (March 2015) - Piñero, Federico; Marciano, Sebastián; Anders, Margarita; Orozco, Federico; Zerega, Alina; Cabrera, Carla Ramirez; Baña, Matías Tisi; Gil, Octavio; Andriani, Oscar; de Santibañes, Eduardo; McCormack, Lucas; Gadano, Adrián; et al.
Abstract : Background and aims: Surveillance during liver transplantation (LT) waiting list has scarcely been reported in South America. We aimed to describe hepatocellular carcinoma (HCC) surveillance during the LT waiting list in the daily practice. Patients and methods: A multicenter retrospective analysis in cirrhotic patients was carried out. All patients underwent an ultrasound (US) every 6 months and the last pre-LT US was compared with explanted liver findings. A false-negative case was considered when incidentally found HCC (iHCC) was detected, whereas a false-positive case was considered when HCC diagnosed before LT (cHCC) was not confirmed in the explanted liver. US performance was assessed after excluding cHCC patients referred to transplant evaluation. Results: Of 643 patients, 129 had HCC, of whom 92 had cHCC (71.3%) and 37 had iHCC (28.7%). Five patients (5.4%) had nonconfirmed cHCC ( n =3 regenerative nodules, n =1 biliary hamartoma, and n =1 cholangiocarcinoma). Patients with iHCC had a higher MELD score (23±10 vs. 15±10; P <0.0001), and were more frequently Child–Pugh C (62.2 vs. 36.6%; P =0.006) compared with patients with cHCC. The number of US performed during waiting list was 1.7±1.6 (median 1.0). During transplant waiting list, the sensitivity and specificity of US were 33 and 99%, with positive and negative predictive values of 0.89 and 0.93, respectively. Multivariate analysis showed that the strongest variable related to iHCC finding was pre-LT Child–Pugh C status (OR 3.5; P =0.004). Conclusion: Screening for liver cancer remains an important issue during transplant waiting list. However, the US screening method should be reviewed particularly for Child–Pugh C patients.